2020
DOI: 10.1021/acsnano.0c02979
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Gatable Superconducting Shadow Junctions

Abstract: Gate-tunable junctions are key elements in quantum devices based on hybrid semiconductor–superconductor materials. They serve multiple purposes ranging from tunnel spectroscopy probes to voltage-controlled qubit operations in gatemon and topological qubits. Common to all is that junction transparency plays a critical role. In this study, we grow single-crystalline InAs, InSb, and InAs1–x Sb x semiconductor nanowires with epitaxial Al, Sn, and Pb superconductors and in situ shadowed junctions in a single-step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 49 publications
(74 reference statements)
6
90
0
Order By: Relevance
“…On the verge in between basic material research and technological implementation, novel fabrication techniques are used to pursue a high device quality with high yield ( 17 , 19 ). One main aspect for superconducting topological hybrid devices is to ensure a highly transparent interface between the topological matter and the superconducting metal deposited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the verge in between basic material research and technological implementation, novel fabrication techniques are used to pursue a high device quality with high yield ( 17 , 19 ). One main aspect for superconducting topological hybrid devices is to ensure a highly transparent interface between the topological matter and the superconducting metal deposited.…”
Section: Introductionmentioning
confidence: 99%
“…One main aspect for superconducting topological hybrid devices is to ensure a highly transparent interface between the topological matter and the superconducting metal deposited. Complex in situ deposition techniques have been developed in these regards, which have been reported to lead to contaminant-free interfaces, high transparencies, and a strong proximity coupling ( 17 , 19 ). We recently reported on molecular beam epitaxy (MBE)–grown, in situ defined TI Josephson junctions on ternary compound (Bi 0.06 Sb 0.94 ) 2 Te 3 (BST) thin films ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we demonstrate a new concept for merging the NC geometry with pre-defined substrate structures to enable in situ patterning of epitaxial superconductors, which have been shown to substantially enhance the performance of hybrid devices. [22][23][24]…”
Section: Doi: 101002/adma202100078mentioning
confidence: 99%
“…[8] However the fragility of InSb is a challenge for devices based on InSb/Al epitaxial hybrids as all known etchings of Al also severely damages the InSb semiconductor and degrade device performance. Recently, in situ "shadow" approaches [18,[21][22][23][24] have been developed allowing patterning of epitaxial superconductor growth, yielding reproducible transport characteristics and observations of ballistic transport at B = 0 T for single NWs. These in situ shadow concepts, developed for single NWs, are however, incompatible with the NC geometry, where controlled shadows of the central junction region are required for most applications.…”
Section: In Situ Shadow Patterning Of Nanocrossesmentioning
confidence: 99%
“…However, recently it was demonstrated that closely separated superconducting electrodes can also be achieved by shadow evaporation technique, i.e. either by using a nanowire which crosses another [25][26][27] or using a patterned, suspended SiO 2 layer as a shadow or stencil mask. 18,22 All of these methods, have a common trait to potentially reach the so-called short channel limit, in which the current through the device is only carried by a single Andreev bound state.…”
Section: Introductionmentioning
confidence: 99%